Accelerometer Derived Activity Counts and Oxygen Consumption between Young and Older Individuals. (25th May 2014) - Whitcher, Lucas; Papadopoulos, Charilaos
Abstract : The purpose of this investigation was to compare accelerometer activity counts and oxygen consumption between young and elderly individuals. Sixteen young (21.3 ± 2.5  yrs) and sixteen elderly (66.6 ± 2.9  yrs) participants completed 30 minutes of resting oxygen consumption to determine resting metabolic rate and four 6 min walking intensities ranging from 27 to 94 m· min −1 . Resting oxygen uptake was significantly lower for the older participants. Exercise oxygen consumption was significantly higher for the elderly group. There were no significant differences in activity counts between groups at each of the exercise intensities. When using measured resting metabolic rate, activity counts of 824 and 2207 counts· min −1 were associated with moderate (3 METs) physical activity intensity for the older and young participants, respectively. However, using standard resting metabolic rate (3.5 mL· kg −1 · min −1 ), activity counts of 784 and 2009 counts· min −1 were associated with moderate physical activity intensity for the elderly and young participants, respectively. These findings indicate that activity counts are similar across age groups even though the oxygen consumption of exercise is greater among elderly individuals.